Phytochemical Screening, Antioxidant Test and Antimicrobial Test of Streptococcus Mutans and Candida Albicans from Extracts of Ultrasound Assisted Extraction of Red Betel Leaves (Piper Ornatum N. E. Br) - Djarot, Prasetyorini; Utami, Novi Fajar; Mahyun, Siti; Annisa, Julmudia Nurul; Mutmaiah, Siti Nafsiatul (Corespub, 2025)
Red betel (Piper ornatum) is an ornamental plant with potential antibacterial and antioxidant properties due to its bioactive compounds, including alkaloids, flavonoids, steroids, triterpenoids, saponins, and tannins. This study aimed to determine the relationship between flavonoid content, antioxidant activity, and antimicrobial activity in red betel leaves. Ultrasound-Assisted Extraction (UAE) was employed using three solvents of varying polarity: n-hexane (non-polar), ethyl acetate (semi-polar), and ethanol (polar). Total flavonoid content was determined spectrophotometrically based on flavonoids' ability to form complexes with AlCl3. Antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. Antibacterial and antifungal properties were evaluated through Minimum Inhibitory Concentration (MIC) and Zone of Inhibition (ZOI) tests. MIC was determined using the agar dilution method, while ZOI was measured using the disc diffusion method. Results showed that the 96% ethanol extract yielded the highest flavonoid content (4.748%) and the strongest antioxidant activity (IC50 = 47.185 ppm, classified as very strong). The n-hexane extract at 25% concentration exhibited the best antibacterial activity against Streptococcus mutans (ZOI = 17.43 mm), while the 96% ethanol extract at 25% concentration demonstrated the highest antifungal activity against Candida albicans (ZOI = 17.02 mm). In conclusion, red betel leaf extracts show promising potential as strong antioxidants and antimicrobial agents against C. albicans and S. mutans.